LITERATURE REVIEW: Pengaruh Penerapan Protokol ERAS (Enhanced Recovery After Surgery) Terhadap Length of Stay pada Pasien Pasca Pembedahan - Miladina Zahra Aulia; Risal Wintoko; Sutyarso Sutyarso; Anggraeni Janar Wulan (Medula, 2023)
Surgery is a follow-up action of invasive emergency treatment by making an incision in a certain part of the body so that it can reach the target organ, after which it ends with closing or suturing the wound. The patient will experience the postoperative impact which is limited movement due to the pain felt after the surgical wound. Furthermore, because the patient cannot mobilize properly, it will affect wound healing. This has an impact on the patient's length of stay which is getting longer and will ultimately make the patient's quality of life worse. Patients with prolonged length of stay are at risk of developing other complications because the patient experiences a decrease in functional status during hospitalization. In addition, the impact of an extended length of stay can increase the financing burden for the hospital. Therefore, efforts are needed to accelerate effective post-surgical healing by implementing the ERAS (Enhanced Recovery After Surgery) protocol. ERAS is a multidisciplinary-based perioperative management protocol with the aim that postoperative patients experience immediate recovery by maintaining postoperative organ function, reducing stress response during surgery, and reducing morbidity in surgery. In several studies, the length of stay of postoperative patients applying the ERAS protocol was shorter than that of patients who did not use the ERAS protocol. This is because in the ERAS protocol, preparations are made for patients starting from pre-admission, pre-operative, intra-operative, and post-operative, each of which has components that can have an impact on accelerating post-operative patient recovery so that the patient's length of stay becomes shorter.